Is the Church Untruth? Reading Kierkegaard’s Critique of the Crowd in Light of the New Testament Ecclesiology - Lumbanbatu, Kornelius (STFT Jakarta, Indonesia, 2024)
This study seeks to enrich the contemporary discourse of the thought of Søren Kierkegaard by positing an analysis of the ecclesiology of the New Testament according to the Danish thinker’s critique of the crowd. Through a literature study on both topics, I try to indicate whether Kierkegaard would consider the church untruth based on its similarity to his depiction of the crowd. Such a literature study is delineated in a three-segmented explanation, each focusing on Kierkegaard’s view of the crowd, the New Testament portrayal of the church, and the intersections between the two. Eventually, I conclude that Kierkegaard would indeed perceive the church as an embodiment of the crowd and consider it untruth. Such a conclusion demands further study on the validity of Kierkegaard’s understanding of Christ, as it confirms the potential aporia that haunts his critique of the crowd when read in light of the New Testament ecclesiology.